Genetics of canine diabetes mellitus part 1: Phenotypes of disease. (April 2021) - Denyer, Alice L.; Catchpole, Brian; Davison, Lucy J.
Highlights: The multiple forms of human diabetes mellitus (DM) have different underlying causes. Canine DM is likely to be heterogeneous, similar to human DM. Identifying genetic risk factors is important to improve understanding of canine DM. Greater understanding of canine DM aetiology will improve disease classification. Increasing precise disease phenotyping will greatly benefit genetic studies. Abstract: This two-part article discusses the mechanisms by which genetic variation can influence the risk of complex diseases, with a focus on canine diabetes mellitus. In Part 1, presented here, the importance of accurate methods for classifying different types of diabetes will be discussed, since this underpins the selection of cases and controls for genetic studies. Part 2 will focus on our current understanding of the genes involved in diabetes risk, and the way in which new genome sequencing technologies are poised to reveal new diabetes genes in veterinary species.